Schulabgänger ohne Hauptschulabschluss: Regionale Disparitäten eines wachsenden Problempotenzials - Franz, Peter; Lang, Cornelia (Raumforschung und Raumordnung | Spatial Research and Planning, 2000)
This rise in the number of complaints coming both from entrepreneurs and from business organisations about the unsatisfactory levels of education displayed by school-leavers suggests a failure to match the increased demand for „human capital„ with sufficient supply of the right quality. One indicator of this problem is the rise since the beginning of the 1990s — both in absolute terms and proportionately — in the number of young people leaving school without even minimal qualifications — i.e. the certificate of achievement awarded by secondary modern schools, the so-called Hauptschulabschluss. Young males are almost twice as likely to fall into this category as young females; in eastern Germany young Germans are more likely to leave school without qualifications than in the west of the country. The disparities among the various Länder cannot be accounted for satisfactorily solely by reference to per capita spending or class size. Within the three Länder subjected to closer examination, Thuringia, Saxony-Anhalt and Brandenburg, there are striking differences from county to county in the percentage of school-leavers who have failed to attain the Hauptschulabschluss. Among a number of different variables which may be assumed to have produced these regional disparities, one which appears to contribute to lowering the proportion of young people leaving school without qualifications is the range of educational opportunities available in a particular county. Counties which consistently record above-average rates for male school-leavers without qualifications are called upon to respond through appropriate educational policies.